Saúde mental pós pandemia Covid-19: uma análise sobre o acesso e cuidado na atenção primária à saúde - Silva, Clécia Vilas Bôas Cerqueira (2024)
The COVID-19 pandemic has not only had an impact on people's physical health, but has also raised concerns about the worsening of mental health symptoms in the population. Translating this discussion to primary healthcare workers, there is concern about the impact on their mental health and the population they serve, as PHCs play a fundamental role in healthcare delivery and care, especially as they are the main gateway of the healthcare system. Therefore, this research aims to analyze the process of care and access offered to users with mental health care needs in PHC in the municipality of Várzea da Roça - Ba. It is a qualitative, exploratory field research conducted with doctors and nurses who form the family health teams and PHC users with mental health needs in the municipality. Data collection was conducted through semistructured interviews with staff and users and a focus group with staff. After analyzing the collected data, four categories were formed, which will be discussed: Access and organization of the provision of mental health interventions in PHC, highlighting the ease of access described by users and staff; Relationship of the pandemic to mental health care and self-care, confirming the impact of the pandemic on mental health issues related to the lack of self-care interventions by the majority of professionals; Production of mental health care in PHC: the diagnosis of work qualifications for mental health care showed that professionals, even if they feel prepared, address the need for professional qualifications to work with the mentally ill in PHC. In this sense, the present research allowed us to understand the approach to mental health in PHC in the community by making visible the characteristics of small communities and providing an opportunity to reflect on them. It made visible the need for intervention and qualification of mental health assistance. The study aims to contribute to meeting the community's needs after COVID-19 in the PHC environment.